Perbedaan Kemampuan Komunikasi Matematis Siswa Perempuan dan Laki-Laki pada Pembelajaran Inside Outside Circle - Rahma Khumaira; Hendra Kartika; Lessa Roesdiana (Mandalika Mathematics and Educations Journal, 2026)
Mathematical communication skills are among the competencies that students must possess during the learning process. However, there are still variations in these skills, one of which is related to gender. Therefore, it is necessary to conduct a study on the differences in mathematical communication skills between female and male students in mathematics learning. This study was conducted to determine the differences in mathematical communication skills between female and male students using the Inside Outside Circle (IOC) learning model. This study employed a quantitative approach and a comparative method. The research subjects consisted of 30 students who had participated in Inside Outside Circle instruction, divided into 15 female students and 15 male students. A mathematical communication skills test was used as the instrument. Data analysis utilized descriptive statistics, prerequisite tests, and inferential statistics. Based on the Independent Samples t-Test under the assumption of unequal variances (0.004 < 0.05), there was a significant difference between the two groups. Furthermore, the mean mathematical communication skills scores indicated that female students scored higher than male students. Thus, the results of this study indicate a difference in mathematical communication skills between female and male students, with female students demonstrating higher proficiency. Keywords: mathematical communication skills; female and male students; inside-outside circle learning model.